TROMBOEMBOLISMO ARTERIAL FELINO: RELATO DE CASO - Miranda, Kaiane Lorenzi; Vaccarin, Charline Vanessa; Lusa, Fabrieli Tatiane; Lusa, Fabrieli Tatiane; Festugatto, Rafael; Pinheiro, Fernanda (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.